Curb your enthusiasm. The complete fifth season [videorecording (DVD)] - David, Larry (Home Box Office, 2006)
Larry David has it all - except, perhaps, his identity. This season, Larry takes a sentimental journey in search of his roots, stepping on a few toes along the way.